Felty’s syndrome - Wegscheider, Christoph; Ferincz, Vera; Schöls, Karin; Maieron, Andreas (Frontiers in Medicine, 2023)
Felty’s syndrome was first described in 1924 by the US-American physician Augustus Roi Felty as a triad of rheumatoid arthritis, splenomegaly and leucopenia. Even nearly 100 years later, this rare syndrome is still paralleled by diagnostic and therapeutic challenges and its pathogenesis is incompletely understood. Neutropenia with potentially life-threatening infections is the main problem and several pathomechanisms like Fas-mediated apoptosis, anti-neutrophil antibodies, anti-G-CSF antibodies, neutrophil consumption in the context of NETosis and suppression of granulopoiesis by T-LGLs have been suggested. Felty’s syndrome has various differential diagnoses as splenomegaly and cytopenia are common features of different infectious diseases, malignancies and autoimmune disorders. Additionally, benign clonal T-/NK-LGL lymphocytosis is increasingly noticed in Felty’s syndrome, which further complicates diagnosis. Today’s treatment options are still sparse and are largely based on case reports and small case series. Methotrexate is the mainstay of therapy, followed by rituximab, but there is less evidence for alternatives in the case of adverse reactions or failure of these drugs. This article gives an updated review about Felty’s syndrome including its pathogenesis and treatment options.